The Influence of Image Differentiation Strategy and Innovation Product to Competitive Advantage Creative Industries in Cimahi City - Muhammad Agung Dharmajaya (GoAcademica Research & Publishing, 2025)
The creative industry plays a strategic role in driving economic growth in the region, particularly in Cimahi City, known as one of the centers of creative industry development in West Java. Facing increasingly fierce competition, creative industry players strive to improve or maintain sustainable competitive advantage. This study aims to analyze the influence of image differentiation strategies and product innovation on the competitive advantage of the creative industry in Cimahi City. The research method used is a quantitative method with a descriptive and verified approach. Data were obtained through distributing questionnaires to creative industry players in Cimahi City. The data analysis technique used multiple linear regression analysis to test the partial and simultaneous effects between variables. The results show that image differentiation strategies have a positive and significant influence on competitive advantage, product innovation also has a positive and significant influence on competitive advantage, and simultaneously image differentiation strategies and product innovation have a significant influence on the competitive advantage of the creative industry in Cimahi City. These findings indicate that strengthening a unique image and sustainable product innovation are important factors in increasing the competitiveness of the creative industry.